PENDAHULUAN HUKUM FEE KAFALAH PADA LEMBAGA KEUANGAN SYARIAH PERSPEKTIF FIQIH : KONSEP KAFALAH DALAM FIQH MUAMALAH - Reza Shefiadini Abadi Dini (Sekolah Tinggi Ilmu Syariah Darul Falah Bondowoso, 2023)
Islamic Financial Institution is a financial institution which as its operational principle adheres to sharia principles. There are several types of contract products at Islamic Financial Institutions. Among the many products is the product on the contract that can KASBANA : Jurnal Hukum Ekonomi Syariah Volume 3, No.1. Januari 2023, Hlm. abc-def DOI : https://doi.org/10.53948/kasbana.v3i1.xx 2 p-ISSN: 2774-3187 e-ISSN: 2774-3179 be implemented, namely kafalah. What is meant by kafalah is a guarantee given by the guarantor, commonly called kafil, to the party giving the debt (makful lahu) in order to carry out the responsibilities of the indebted party. In the LKS kafalah contract, it can be applied to Bank Guarantee applications and Letters of Credit. Each contract product must apply kafalah practices, all of which must have a fee. However, there are still many people who are confused about the legal relationship between the kafalah fee and the Islamic Financial Institution. The research uses library research or literature research, namely data that is mostly sourced from books, journals or others related to kafalah. The results of research regarding legal fees on LKS from the perspective of fiqh is that there are differences of opinion of the Islamic scholars. Basically, the wakalah contract is a taboo contract, not a tijari contract, which always gets a fee. With these differences, some fiqh scholars do not allow it. Besides that, some scholars also allow fees because if there is no fee, it will not make benefits or often referred to as benefit.